Following the Fate In Vivo of COPI Vesicles Generated In Vitro - Rutz, Christoph (2009)
COPI vesicles are a class of transport carriers that function in the early secretory pathway. Their fate and function are still controversial. This includes their contribution to bidirectional transport within the Golgi apparatus and their role during cell division. Here we describe a method that should address several open questions about the fate and function of COPI vesicles in vivo. To this end, fluorescently labeled COPI vesicles were generated in vitro from isolated rat liver Golgi membranes, labeled with the fluorescent dyes Alexa-488 or Alexa-568. These vesicles appeared to be active and colocalized with endogenous Golgi membranes within 30 min after microinjection into mammalian cells. The COPI vesicle-derived labeled membrane proteins could be classified into two types that behaved like endogenous proteins after Brefeldin A treatment.